SQL Server 2022 Query performance tuning : troubleshoot and optimize Query performance - Fritchey, Grant (ITpro collection, 2022)
Troubleshoot slow-performing queries and make them run faster. Database administrators and SQL developers are constantly under pressure to provide more speed. This new edition has been redesigned and rewritten from scratch based on the last 15 years of learning, knowledge, and experience accumulated by the author. The book Includes expanded information on using extended events, automatic execution plan correction, and other advanced features now available in SQL Server. These modern features are covered while still providing the necessary fundamentals to better understand how statistics and indexes affect query performance. The book gives you knowledge and tools to help you identify poorly performing queries and understand the possible causes of that poor performance. The book also provides mechanisms for resolving the issues identified, whether on-premises, in containers, or on cloud platform providers. You'll learn about key fundamentals, such as statistics, data distribution, cardinality, and parameter sniffing. You'll learn to analyze and design your indexes and your queries using best practices that ward off performance problems before they occur. You'll also learn to use important modern features, such as Query Store to manage and control execution plans, the automated performance tuning feature set, and memory-optimized OLTP tables and procedures. You will be able to troubleshoot in a systematic way. Query tuning doesn't have to be difficult. This book helps you to make it much easier. What You Will Learn Use Query Store to understand and easily change query performance Recognize and eliminate bottlenecks leading to slow performance Tune queries whether on-premises, in containers, or on cloud platform providers Implement best practices in T-SQL to minimize performance risk Design in the performance that you need through careful query and index design Understand how built-in, automatic tuning can assist your performance enhancement efforts Protect query performance during upgrades to the newer versions of SQL Server Who This Book Is For Developers and database administrators with responsibility for query performance in SQL Server environments, and anyone responsible for writing or creating T-SQL queries and in need of insight into bottlenecks (including how to identify them, understand them, and eliminate them).